Impact of on-field repeated sprint training on aerobic fitness and anaerobic performance in football athletes: a matched-pair design - Gupta, R.; Rizvi, M. R.; Sharma, A.; Sharma, S.; Shaik, A. R.; Seyam, M. K.; Raza, S.; Alshahrani, M. S.; Alkhamis, B. A.; Alnakhli, H. H.; Alsalm, L. M.; Ahmad, F.; et al. (PLOS ONE, 2025)
Background Repeated sprint ability (RSA) is essential for football performance, especially in maintaining high-intensity efforts throughout a match. Repeated sprint training (RST) improves both aerobic and anaerobic capacities; however, its effects on players in different positional roles remain underexplored, particularly with regard to tailored conditioning protocols.